Immediate Effect of Muscle Energy Technique and Proprioceptive Neuromuscular Facilitation Stretching on Calf Muscle Flexibility Among University Level Recreational Athletes – A Randomized Clinical Trial - Bhavika P., Gohel; R., Kamalakannan; Kamesh, C.; Vinosh Kumar, Purushothaman (INTI International University, 2024)
[Objective] To assess and compare the immediate impact of muscle energy technique (MET) and proprioceptive neuromuscular facilitation (PNF) stretching on calf muscle flexibility in recreational athletes. [Method] A total 30 individuals participating in recreational activities were divided into two groups: Group A, which followed the MET protocol, and Group B which followed the PNF protocol. The range of motion (ROM) of ankle dorsiflexion was evaluated before and after the intervention. [Results] Analysis of data was conducted using non-parametric testing. The data within the group was examined using Wilcoxon signed rank test. The data was compared between group with Mann Whitney U test. The outcome was determined to be statistically significant (p value 0.001) for every group. Inter group analysis revealed a p value <0.05, indicating a substantial disparity in the effects of the two therapies. [Conclusion] In conclusion, both MET and PNF stretching techniques have an immediate impact on the flexibility calf muscle. However, MET has been demonstrated to be more efficient than PNF stretching in enhancing flexibility of the calf muscle.